Mycobacterial Evolution Intersects With Host Tolerance - Saelens, Joseph W.; Viswanathan, Gopinath; Tobin, David M. (Frontiers in Immunology, 2019)
Over the past 200 years, tuberculosis (TB) has caused more deaths than any other infectious disease and currently infects more people than it has at any other time in human history. Mycobacterium tuberculosis (Mtb), the etiologic agent of TB, is an obligate human pathogen that has evolved through the millennia to become an archetypal human-adapted pathogen. This review focuses on the evolutionary framework by which Mtb emerged as a specialized human pathogen and applies this perspective to the emergence of specific lineages that drive global TB burden. We consider how evolutionary pressures, including transmission dynamics, host tolerance, and human population patterns, may have shaped the evolution of diverse mycobacterial genomes.